Optimalisasi Potensi Wisata Melalui Edusport Tourism di Telaga Ngrejek Gunung Kidul untuk Mewujudkan Desa Wisata - Nurhadi Santoso; Ratna Kumala Setyaningrum; Masri Masri; Agus Wiyanto (Jurnal Pengabdian Olahraga Masyarakat, 2023)
The purpose of this community service is to raise awareness among the community regarding the existing potential of Ngrejek Lake and to optimize the tourism management by the youth organization (karang taruna) and the community empowerment group (Pokdasawisma), through providing assistance in terms of Edu-Sport Tourism and promoting the "overflowing market" as part of the enchantment of the tourism that can be managed by the local residents. The implementation method involves delivering materials about community-based tourism (Pokdarwis) and Edu-Sport Tourism. The delivery pattern of the materials is more focused on presentation, discussion, and question and answer sessions, with the aim of developing Ngrejek Lake as a recreational area and Edu-Sport Tourism destination for the local community. The primary subjects of this target are the 23 members of the youth organization and the 7 village officials. Prior to the material delivery, a pretest is conducted, followed by a post-test after the implementation, specifically assessing the development of Ngrejek Lake as a recreational area and Edu-Sport Tourism destination. The pretest results show that the average understanding of the village officials regarding tourism village development is 49.43, and the average post-test result is 55.14. Similarly, the pretest results for the youth organization members show an average understanding of 51.35, with an average post-test result of 54.96. The comprehension of tourism village development has improved for both the village officials and the youth organization members in the efforts to develop Ngrejek Lake as a recreational area and Edu-Sport Tourism destination.ABSTRAKTujuan pengabdian ini adalah meningkatkan kesadaran masyarakat terhadap potensi yang ada di Telaga Ngrejek, serta untuk mengoptimalkan pengelolaan wisata oleh karang taruna dan Pokdasawisma dengan memberikan pendampingan mengenai Edu-Sport Tourism juga sosialisasi pasar tumpah sebagai bagian dari pesona wisata yang bisa dikelola olah warga. Metode pelaksanaan berupa penyampaian materi tentang Pokdarwis, dan Edu-Sport Tourism. Pola penyampaian materi lebih bersifat pemaparan materi, diskusi dan tanya jawab dalam pengembangan Telaga Ngrejek sebagai tempat rekreasi dan Edu-Sport Tourism bagi warga masyarakat. Subjek sasaran pertama ini karang taruna yang berjumlah 23 orang dan perangkat desa ada 7 orang. Sebelum pelaksanaan penyampaian materi dilakukan pretest dan sesudah pelaksanaan dilakukan postest tentang pengembangan Telaga Ngrejek untuk tempat rekreasi dan Edu-Sport Tourism. Hasil pretest pemahaman desa wisata pegawai perangkat desa dengan rerata 49,43 dan rerata postestnya 55,14. Sedangakan hasil pretest pemahaman desa wisata karang taruna dengan rerata 51.35 dan rerata postestnya 54.96. Pemahanan pengembangan desa wisata baik pegawai perangkat desa dan karang taruna meningkat dalam upaya pengembangan Telaga Ngrejek menjadi tempat rekerasi dan Edu-Sport Tourism.